Penerapan Pendekatan STEM pada Materi Laju Reaksi Siswa Kelas XI - Dhamas Mega Amarlita (Journal on Education, 2023)
The development of existing technology increases competitiveness in various aspects, including in the field of education. This makes an educator required to be able to continue to innovate in the learning process, one of which is by implementing learning that includes creative, critical thinking and collaboration. One of them is by applying the STEM approach in the implementation of learning. This STEM approach is suitable to be applied to chemistry subjects because this approach includes science, namely learning activities carried out through direct experimental evidence. This research was conducted on 20 students of class XI at MA Matlaul Anwar, who were taken by purposive sampling. With the results of 95% of students can understand the material well and very well.